Is mediation a scientific discipline? Theoretical and practical perspectives - Blanco Carrasco, M.; Arias Astray, A.; Ferreira, J. M. L. (Conflict Resolution Quarterly, 2025)
The main objective of this study is to determine whether mediation is regarded as an autonomous discipline from both academic and professional standpoints. To achieve this, the study initially conducted a review of the most recent literature on the subject, followed by gathering opinions from experts, professionals, and trainers across eight different countries through in-depth interviews and discussion groups. Among the primary findings of the research, it becomes apparent that while mediation remains a relatively underexplored topic, existing literature suggests that it possesses elements to assert its status as a scientific discipline, evidenced by its own axioms, paradigms, models, and methodologies. However, the professionals and experts consulted contend that it falls short of being classified as such. They cite several challenges, including the scarcity of real cases for investigation, the disconnect between theory and professional application, and the need for enhanced quality in scientific research to surmount the stagnation it has encountered for years.